The modulation of steady-state responses by transcranial alternating current stimulation: a scoping review - Mockevičius, Aurimas; Bjekić, Jovana; Griškova-Bulanova, Inga (Frontiers in Systems Neuroscience, 2025)
Transcranial alternating current stimulation (tACS) is a non-invasive technique that modulates brain oscillatory activity in a frequency-specific manner, offering potential for improving sensory and cognitive functions. Steady-state responses (SSRs), which are periodic neural responses to rhythmic sensory stimulation, provide a robust and objective means to assess tACS effects. The present work systematically reviews the existing literature on tACS modulation of SSR. 16 studies that used either auditory (ASSR) or visual (SSVEP) SSR were included in the review. Findings indicate that tACS can enhance or suppress SSRs depending on stimulation parameters. Although ASSR studies reported mixed findings, generally, gamma tACS enhanced ASSR, whereas tACS at lower frequencies resulted in ASSR inhibition. For SSVEPs, modulation was shown to be phase- and frequency-dependent, with congruent tACS and flicker frequencies producing the most reliable effects. Despite methodological heterogeneity and inconsistent results, the reviewed evidence highlights the potential of SSRs as sensitive markers of tACS outcomes. Future studies should aim for well-planned protocols tailored to specific aims and target populations.